2018
DOI: 10.1111/sms.13068
|View full text |Cite
|
Sign up to set email alerts
|

The effects of flexibility training on exercise‐induced muscle damage in young men with limited hamstrings flexibility

Abstract: Adaptations to 6 weeks of supervised hamstring stretching training and its potential impact on symptoms of eccentric exercise-induced muscle damage (EIMD) were studied in 10 young, untrained men with limited hamstrings flexibility. Participants performed unilateral flexibility training (experimental leg; EL) on an isokinetic dynamometer, while the contralateral limb acted as control (CL). Hip range of motion (ROM), passive, isometric, and concentric torques, active optimum angle, and biceps femoris and semiten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…However, there are conflicting reports on the effectiveness of flexibility training on DOMS in the literature. Brusco et al (102) did not find any difference in soreness reduction after 6 weeks of hamstrings stretching exercise in individuals with limited hamstrings flexibility. This study differed from the study of Chen et al (101) in that the stretching was not performed with maximal intensity (stretches were performed to a constant joint angle, rather than to maximum tolerance).…”
Section: Effects Of Stretching On Delayed Onset Muscle Soreness (Doms)mentioning
confidence: 87%
“…However, there are conflicting reports on the effectiveness of flexibility training on DOMS in the literature. Brusco et al (102) did not find any difference in soreness reduction after 6 weeks of hamstrings stretching exercise in individuals with limited hamstrings flexibility. This study differed from the study of Chen et al (101) in that the stretching was not performed with maximal intensity (stretches were performed to a constant joint angle, rather than to maximum tolerance).…”
Section: Effects Of Stretching On Delayed Onset Muscle Soreness (Doms)mentioning
confidence: 87%
“…1A; 2, 8, 13,24,42,45,53,63) or plantar flexor (Fig. 1C; 10, 26, 40) stretch tests, although this is sometimes not observed (12,13,27). In cases where an increase in stretch tolerance has been observed, the conclusion can be made that either 1) the sensory feedback received by the central nervous system during the stretch or 2) the conscious or subconscious response to that feedback (i.e., decision as to when to terminate the stretch) was altered (9).…”
Section: Effects Of Passive (Static) Muscle Stretchingmentioning
confidence: 98%
“…For the knee flexors (see example in Fig. 1A), no alteration was observed in the change in torque produced as the joint angle was increased (i.e., joint or MTU stiffness; 42,45,50,53,63) or in either the knee angle at which a specific joint torque was reached (2,8,20) or the joint torque registered at a specific knee angle (12,78); of course, the maximum stiffness may be seen to increase since the MTU is stretched further after training and thus the MTU resists with a greater force according to its passive force-length relationship [see Reid and McNair (63) for example]. These findings conclusively show that passive stiffness measured at specific MTU lengths remains unchanged after chronic knee flexor stretch training lasting several weeks to months.…”
Section: Effects Of Passive (Static) Muscle Stretchingmentioning
confidence: 98%
“…brighter image) has been suggested to represent the accumulation of inflammatory cells between muscle fibers [12,31,70]. Since the infiltration of inflammatory cells is known to peak 3-4 days after a muscle damaging event, various studies have concluded that the increase in echo intensity during that time period allowed them to infer that echo intensity is a measurement of exercise-induced edema and inflammation [3,33,39,40].…”
Section: Muscle Damagementioning
confidence: 99%